2022
DOI: 10.1037/spq0000493
|View full text |Cite
|
Sign up to set email alerts
|

How did the pandemic affect the socio-emotional well-being of Chilean schoolchildren? A longitudinal study.

Abstract: This study investigated the repercussions of coronavirus disease and the subsequent quarantine on the emotional well-being of children in their initial years of formal schooling, with particular emphasis on children with special educational needs (SEN) and children from high and low socioeconomic statuses (SES). This longitudinal study employed the Child Behavior Checklist for ages 6-18 (CBCL) completed by the students' guardians at least once during 2018-2019 and again during 2020. The results showed differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Analyzing the subsamples divided by diagnoses, we found that the adolescents with anxiety disorder, mood disorder, specific learning disorder, behavioral disorder and epilepsy showed a global worsening in all the CBCL scales. In agreement with our data, previous literature studies had shown a worsening of psychological well-being during the lockdown in patients with epilepsy and learning disabilities [ 28 , 29 , 59 , 60 , 61 ] probably due to difficulties with distance learning; in contrast with our results, a larger sample study found that both depressive and anxiety symptoms were lower for adolescents with mood disorders during the pandemic compared to before [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…Analyzing the subsamples divided by diagnoses, we found that the adolescents with anxiety disorder, mood disorder, specific learning disorder, behavioral disorder and epilepsy showed a global worsening in all the CBCL scales. In agreement with our data, previous literature studies had shown a worsening of psychological well-being during the lockdown in patients with epilepsy and learning disabilities [ 28 , 29 , 59 , 60 , 61 ] probably due to difficulties with distance learning; in contrast with our results, a larger sample study found that both depressive and anxiety symptoms were lower for adolescents with mood disorders during the pandemic compared to before [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study reported results for school children in their initial years of school with and without special educational needs and by high and low socioeconomic status (SES) [34]. They described an increase in socio-emotional internalizing problems, with those with special educational needs and low SES most severely affected following quarantine [34]. All groups were also affected by an increase in externalizing problems during the pandemic, however, this did not differ by special educational needs [34].…”
Section: Interpretation In Light Of Other Studiesmentioning
confidence: 94%
“…There is limited literature on the impacts of the COVID-19 pandemic on children with special needs [33]. A longitudinal study of Chilean schoolchildren, with data available before the pandemic (in 2018-2019) and during the early pandemic (in 2020), reported increased internalizing and externalizing problems following quarantine [34]. This study reported results for school children in their initial years of school with and without special educational needs and by high and low socioeconomic status (SES) [34].…”
Section: Interpretation In Light Of Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several international studies describe how the COVID‐19 pandemic has influenced children's social‐emotional well‐being and mental health. For example, Santa‐Cruz et al 2 utilized longitudinal data to explore the repercussions of COVID‐19 quarantines on the emotional well‐being of Chilean children.…”
Section: Covid‐19 School Closures and Socioemotional Well‐beingmentioning
confidence: 99%